1990
DOI: 10.1080/01496399008050385
|View full text |Cite
|
Sign up to set email alerts
|

Pervaporation of Aqueous Ethanol Mixtures through Poly(Dimethyl Siloxane) Membranes

Abstract: The separation of ethanollwater mixtures by pervaporation with a poly(dimethy1 siloxane) membrane has been studied. The membrane exhibited ethanol selectivity during all process runs. Investigations focused on the effects of temperature and permeate-side pressure on membrane transport with dilute ethanol feed solutions. An increase in temperature increased the flux exponentially but had little effect on selectivity. As the permeate-side pressure was increased, the flux decreased. Selectivity did not change app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 14 publications
6
11
0
Order By: Relevance
“…It can be stated at higher ethanol concentration the separation effectiveness of the organophilic pervaporation membranes are decreased, similar tendency have been already published by Slater et al [25], Lazarova et al [27], Vane [34], Chai et al [35] and Fu et al [36]. Table 2, Table 3 and Table 4 summarize the estimated values of transport coefficients, activation energies, exponential parameters and minimized objective functions of the two models.…”
Section: Resultssupporting
confidence: 67%
“…It can be stated at higher ethanol concentration the separation effectiveness of the organophilic pervaporation membranes are decreased, similar tendency have been already published by Slater et al [25], Lazarova et al [27], Vane [34], Chai et al [35] and Fu et al [36]. Table 2, Table 3 and Table 4 summarize the estimated values of transport coefficients, activation energies, exponential parameters and minimized objective functions of the two models.…”
Section: Resultssupporting
confidence: 67%
“…As the feed concentration increased from 5 to 30 wt%, the separation factor decreased from 15.0 to 4.1, and the total flux increased from 452.2 to 818.6 g/m 2 h with the operation temperature of 60°C. The effect of ethanol feed concentration on pervaporation performance of multilayer PDMS/PVDF composite membrane was similar to that of PDMS composite membrane reported in literatures [16][17][18]. As the feed concentration increased, the free volume in PDMS membrane also increased due to the increase of swelling degree of PDMS membranes.…”
Section: Effect Of Ethanol Feed Concentration On Pervaporation Perforsupporting
confidence: 77%
“…However, they usually have poor mechanical strength, and the studies to improve their mechanical properties have been carried out by introducing a siloxane-imide block or graft copolymer structure. [12][13][14][15][16] These studies showed that pervaporation selectivity and permeation flux towards organic compounds decreased with decreasing the fraction of the siloxane group. The observation indicates that polysiloxaneimide homopolymer membranes are expected to show good pervaporation performances, but the pervaporation studies with polysiloxaneimides have not been reported yet.…”
Section: Introductionmentioning
confidence: 96%